Executive Dysfunction and Language Deficits in a Pediatric Patient with OCD and MDD with Suicidality. (30th April 2019) - Yuan, Melissa
Abstract : The role of neuropsychiatric testing in psychiatric disorders is becoming more prominent. Neuropsychological measures that are similar across symptom domains and phenomena such as suicidality may help clinicians guide treatment and tailor therapies to the patient in the most effective way possible. We report the case of a 16-year-old girl who presented with bizarre, intrusive suicidal thoughts in the setting of OCD and MDD. This case is unusual in that we have accurate neuropsychological determination of our patient's language and executive function deficits, and we propose a link between them and her expression of suicidality in the context of OCD and MDD.